A behavior experiment study: Information integration in sensory perception of female suit silhouettes. Issue 1 (2nd January 2017) - Qin, Fang; Jiang, Ying; Liu, Guo-Lian
Abstract: Sensory evaluation of garment silhouettes is comprehensive, and it is an important index in evaluating the sense of clothes. In this paper, a behavior experiment was used to collect data instead of questionnaire in traditional research in garment sensory perception. The results show the main effect of silhouette element and interaction effects between elements on sensory perception were quite different. The information integration in garment silhouette sensory perception was differed in different emotional. The integration model and mathematical model constructed in this paper can provide a basis for integrating other perception information such as color and hand feeling in sensory evaluation of garment. Method in the paper will provide a creative idea for studying garment featured-pattern research in computer vision.